Optimisation of phenolic compounds extraction from misai kucing using RSM - Ainin Sofia, Azni (2015)
Misai kucing or the scientific name is Orthosiphon stamineus contains lots of phenolic compounds such as phenolic acid, flavanoids and antioxidants. These compounds have various benefits likes antifungal, antimicrobial, antitumor and antibacterial. Besides that, people also used it as remedy to treat the diseases. In order to get components from plant materials, normally they used extraction method. The yield of phenolic compounds extraction is dependent on the size of particles, solvent used, extraction method, power irradiation and condition. The method used for this work is microwave assisted extraction was studied by using response surface methodology (RSM) design for optimization. The 2 level factorial and Box behnken design have been used to determine the optimum extraction and to develop a quadratic polynomial. The highest peak for rosmarinic acid from the extraction of misai kucing is 2.203 at 2.00 to 2.30 minutes while the standard peak of rosmarinic acid is at 2.215 at 2.00 o 2.30 minutes. The highest yield of rosmarinic acid (RA) of 24.7971 mg RA/g DW was obtained at 66.6% of aqueous ethanol concentration with 112W microwave power for 3.75 minutes. The yield for total phenolic content (TPC) and total flavonoid content (TFC) are 48.51 mg GAE/g DW and 233.243 mg QE/gDW respectively. The optimum yields were obtained at 54.68% of ethanol at 170W of microwave power for 4.34 minutes. The lower total solid (TS) was produced higher rosmarinic acid per DW of material but higher TS contain more rosmarinic acid and hence it is affect by reduced its solubility in solvent and lower extraction yield. Longer extraction time increased rosmarinic acid extraction yield at lower TS (0.1 g/ml) because longer time needed for rosmarinic acid to diffuse in the solvent. Since solvent is not saturated at lower TS so the extraction process continues and become higher at longer time. The microwave assisted extraction provides rapid extraction of phenolic compounds without significantly compromising the extraction yield.